Asset Legalization Through the Waqf Land Certification Acceleration Program to Realize Legal Certainty in Kaliwungu District, Kudus (Indonesian Journal of Agrarian Law, 2025)
One of the problems that often occurs in the community is that there are still many waqf lands that are not registered so that they have the potential to cause disputes in the future. As happened in Kaliwungu District, where the number of waqf land that has not been certified waqf from 2017-2025 is 37 fields with a land area of 8.443 M² which is spread almost evenly in Kaliwungu District. Based on this data, the Land Office together with the Ministry of Religion Kudus implemented a program to accelerate waqf land certification. This study uses empirical legal research methods. The result of this study is that the implementation of the waqf land certification acceleration program in Kaliwungu District is a form of cooperation between KUA Kaliwungu, the Land Office, and the nazhir. KUA Kaliwungu innovates to implement a waqf service pick-up policy where the process of managing waqf land registration is fully carried out by KUA officers starting from taking requirements at the waqf and nazhir houses to the process of issuing waqf land certificates. The result of this program in Kaliwungu District is in the form of the issuance of waqf certificates on 37 land plots that have not yet received waqf certificates. Thus, this program can provide benefits, especially to the nazhir regarding the certainty of rights to waqf land.